2014
DOI: 10.1002/ciuz.201400695
|View full text |Cite
|
Sign up to set email alerts
|

Die Ostsee atmet auf

Abstract: Phytase is one of the most important feed additive enzymes for monogastric animal, because it hydrolyzes the indigestible phytate in the cereal‐based feedstock to release phosphate as an essential nutrient. To understand its molecular machinery, the three‐dimensional structures of various types of phytases and complexes have been studied extensively. For commercial applications, important properties such as higher catalytic efficiency and higher thermostability are desired. Since a phytase with both beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Of special interest are the transport properties of hydrogen sulde, which appears in many marine environments. [45][46][47] The study of Merkel and Toy (2006) 51 revealed CO 2 /H 2 S selectivities much larger than 1 for peruorinated polymers in contrast to silicone rubber ( Table 1). The reason for this effect is low H 2 S solubility, caused by unfavourable interactions between the penetrant and the uorinated polymer.…”
Section: Effect Of Protective Coating On Response Times and Longterm mentioning
confidence: 97%
“…Of special interest are the transport properties of hydrogen sulde, which appears in many marine environments. [45][46][47] The study of Merkel and Toy (2006) 51 revealed CO 2 /H 2 S selectivities much larger than 1 for peruorinated polymers in contrast to silicone rubber ( Table 1). The reason for this effect is low H 2 S solubility, caused by unfavourable interactions between the penetrant and the uorinated polymer.…”
Section: Effect Of Protective Coating On Response Times and Longterm mentioning
confidence: 97%
“…The total volume change can be separated between the Belt Sea and the Sound Sea (see Methods) and then amounts to 169 and 29 , respectively, giving a ratio of 8:1.4, which is close to the previously estimated ratio of 8:2 30 . The recent volume change is comparable to the volume transport induced by the storms Christian in October 2013 (201 11 ) and Ev and Feliz in March 2014 (203 12 ) and significantly larger than the volume change induced by the storm Xaver in December 2013 (147 11 , 12 ). It has been shown that the consecutive events in late 2013 (storm Christian) and early 2014 (Stroms Ev and Feliz), without being listed as strong MBIs, had an effective ventilation impact in the deep Gotland basin 12 .…”
Section: Resultsmentioning
confidence: 82%
“…Earlier storm events during the last decade, e.g. Christian (October 2013), Xaver (December 2013), Danli, Ev and Feliz (February to March 2014) and their impacts on the volume transport into the Baltic Sea and the oxygenation of the Bornholm Basin were addressed in previous studies 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The total volume change is separated between the Belt Sea and the Sound Sea as 169 and 29 km 3 , giving a ratio of 8:1.4, which is close to the previous ratio of 8:2 14 . The recent volume change is comparable to the volume transport induced by the storms Christian in October 2013 (201 km 3 ) and Ev and Feliz in March 2014 (203 km 3 ) and significantly larger than the volume change induced by the storm Xaver in December 2013 (147 km 3 ) 9 .…”
Section: Calculation Of Volume and Salt Transportmentioning
confidence: 76%
“…The inflows are therefore essential for oxygenating and maintaining the ecosystem of the Baltic Sea 7 . The earlier storm events Christian (October 2013, 8,9 ), Xaver (December 2013, 8,9 ), Danli, Ev and Feliz (February to March 2014, 9 ) and their impacts on the volume transport into the Baltic Sea and the oxygenation of the Bornholm basin were addressed in previous studies.…”
Section: Introductionmentioning
confidence: 99%